Domestic Settler Writing and the Global Nineteenth Century. Issue 1 (1st June 2022) - Wagner, Tamara
Abstract : Domestic settler writing has long remained a largely overlooked by-product of imperial expansion and the resultant exportation of popular culture. Global nineteenth-century studies may offer an opportunity to reconsider this admittedly amorphous set of writing from a newly unifying perspective. Approaching these texts through different lenses does more than bring them to renewed scholarly attention and tease out hitherto unacknowledged aspects. In turn, they can enrich global nineteenth-century studies itself, ensuring that the experience of female settlers, emigrating families, and unaccompanied children are not once again marginalized. This article resituates domestic settler writing within a transoceanic, global field of representations, setting out three specific directions for the critical investigation to proceed: (1) a distant reading to capture patterns, (2) a mapping of the circulation of such colonial reading matter, and (3) a comparative analysis, especially of texts that engage with such exchanges, through intertextual references or rewritings.